2020
DOI: 10.1177/1359105320931186
|View full text |Cite
|
Sign up to set email alerts
|

Do gender, anxiety, or sleep quality predict mindfulness-based stress reduction outcomes?

Abstract: Although mindfulness-based stress reduction (MBSR) can improve health and well-being, less is known about factors that predict outcomes. This prospective observational study examined gender and baseline anxiety and sleep quality as predictors of change in emotion regulation and stress symptoms following an 8-week MBSR program. Women and men reported similar improvement in stress symptoms and cognitive reappraisal, whereas men improved more in emotion suppression. Individuals with higher anxiety and worse sleep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
1
13
0
1
Order By: Relevance
“…We admit that an inclusion of a control group in the mindfulness training experimental design would be more rigorous. Though researchers have found that gender can influence the mindfulness training effect on emotion regulation (Brown et al, 2020), the fact that there was no gender ratio difference between the national and provincial teams relieved us from the suspicion of gender difference confounding. Future studies are still welcomed to explore how gender moderates the effect of mindfulness training in sports of shooting and archery.…”
Section: Discussionmentioning
confidence: 99%
“…We admit that an inclusion of a control group in the mindfulness training experimental design would be more rigorous. Though researchers have found that gender can influence the mindfulness training effect on emotion regulation (Brown et al, 2020), the fact that there was no gender ratio difference between the national and provincial teams relieved us from the suspicion of gender difference confounding. Future studies are still welcomed to explore how gender moderates the effect of mindfulness training in sports of shooting and archery.…”
Section: Discussionmentioning
confidence: 99%
“…Stress responses manifest in chronic arousal and impaired function (Fink, 2017; Selye, 1974), whereas anxiety is a blend of thoughts and feelings characterized by a sense of uncontrollability and unpredictability over potentially adverse life events (Wilson, 1996). Research indicates a positive correlation between stress and anxiety (Al Nima et al, 2013; Brown et al, 2021; Saravanan & Wilks, 2014), and higher stress and anxiety are associated with lower happiness (Schiffrin & Nelson, 2010; Shilpa & Prasad, 2017). Considering that we referred to stress as stress response, we hypothesized that anxiety positively predicts stress (Hypothesis 1) and that stress and anxiety negatively predict happiness (Hypothesis 2): (a) High-stress response levels will be associated with low happiness levels, and (b) high anxiety levels will be associated with low happiness levels.…”
Section: Stress Anxiety Functioning and Copingmentioning
confidence: 99%
“…Thus, further studies should pay more attention to this. Furthermore, a previous study argued that men improved more in emotion suppression than women after MBI [73]. In this study, five selected articles mentioned the different genders of the participants, but none investigated whether the MBI has a different effect on MF between genders, which should be investigated in the future.…”
Section: Discussionmentioning
confidence: 90%